Strong-field frustrated double ionization of argon atoms - Chen, Shi; Chen, Jing; Paulus, Gerhard G.; Kang, Huipeng (Physical Review A, 2020)
Using a three-dimensional semiclassical method, we theoretically investigate frustrated double ionization (FDI) of Ar atoms subjected to strong laser fields. The double-hump photoelectron momentum distribution generated from FDI observed in a recent experiment [S. Larimian, Phys. Rev. Research 2, 013021 (2020)2643-156410.1103/PhysRevResearch.2.013021] is reproduced by our simulation. We confirm that the observed spectrum is due to recollision. The laser intensity dependence of FDI is investigated. We reveal that the doubly excited states of Ar atoms and excited states of Ar+ are the dominant pathways for producing FDI at relatively low and high intensities, respectively. The information of which pathway leads to FDI is encoded in the electron momentum distributions. Our work demonstrates that FDI is a general strong-field physical process accompanied with nonsequential double ionization and it can be well understood within the context of recollision scenario.
CRIS-Team Scopus Importer:2023-04-20